Pancreatic Tuberculosis: Diagnostic Challenges and Management Considerations - Gohil, Ravi; Chaudhary, Pragnya (Journal of Neonatal Surgery, 2025)
Background Individuals develop pancreatic tuberculosis extremely rarely among extrapulmonary tuberculosis manifestations because doctors find it hard to diagnose because of nonspecific clinical features. The disease presents symptoms that resemble pancreatic cancers which delays the correct medical treatment. The identification of accurate diagnosis is fundamental before starting anti-tuberculosis treatment to prevent delayed medical interventions. Methods We reviewed pancreatic tuberculosis cases treated at a tertiary care center from January 2015 to December 2022. Medical records received combination analysis together with imaging findings and laboratory data, histopathology findings and treatment outcomes. This study aimed to analyze symptom manifestations at presentation while assessing diagnostic assessment methods and therapeutic decision-making elements besides examining ATT treatment effects on patients. Results Among 42 patients who fulfilled the inclusion criteria, abdominal pain and weight loss were the most prevalent presenting symptoms. Imaging studies often revealed pancreatic masses or pseudocystic changes in the head or body of the pancreas, frequently mimicking malignant lesions. Endoscopic ultrasound (EUS)-guided biopsy was the most reliable diagnostic modality, offering histopathological evidence of caseating granulomas. All patients commenced on standard ATT demonstrated significant clinical improvement, with resolution of imaging abnormalities in the majority by six months of therapy. Only two patients required surgical exploration due to complications. No mortality was directly attributed to pancreatic TB. Conclusion Pancreatic TB requires a high index of suspicion in patients presenting with pancreatic masses, particularly in endemic areas or immunocompromised populations. EUS-guided biopsy and histopathological confirmation are key to avoiding misdiagnosis and unnecessary interventions. Timely initiation of ATT can lead to excellent clinical outcomes. Further studies are needed to optimize diagnosis and management protocols.